EFFECT OF NOMINAL GROUP TECHNIQUE OF BRAINSTORMING ON THE ACHIEVEMENT OF SECONDARY SCHOOL BIOLOGY STUDENTS IN ANAMBRA STATE, NIGERIA - Osuafor, Abigail M.; Ogbaga, Onyinye, A. (PEOPLE: International Journal of Social Sciences, 2016)
Poor performance of students in examinations is most times blamed on use of inappropriate teaching methods. Consequently, the search for appropriate methods for classroom instruction has continued to engage the attention of researchers. Hence, this study was aimed at investigating the ‘Effect of Nominal Group Technique of Brainstorming on the achievement of Secondary School Biology students in Anambra state Nigeria’. Two research questions and two hypotheses guided the study. The quasi-experimental study adopted a pretest post-test non-equivalent control group design. The sample consists of 80 Senior Secondary Two (SS 11) biology students from two intact classes randomly drawn from two co-educational schools. One class was assigned experimental group and the other control. An instrument tagged Biology Achievement Test was validated and used for data collection. Its reliability co-efficient was 0.72. Results showed that Students taught using Nominal Group Technique (NGT) performed significantly better than those taught using Lecture method and there was no significant difference in biology achievement test scores of male and female students taught using NGT. The paper therefore concluded that Nominal Group Technique enhanced achievement of biology students irrespective of gender.